Efficacy of lemongrass (Cymbopogon citratus DC Stapf) and wild spikenard (Hyptis suaveolens L. Poit) compost on the productivity of cowpea (Vigna unguiculata L. Walp) - Olasan, O.J.; Aguoru, C.U.; Omoigui, L.O.; Ngbada, N.A.; Agbulu, I.N. (2025)
This study compared the effects of composts from lemongrass (Cymbopogon citratus) (CCT), wild spikenard (Hyptis suaveolens) (HYS) and NPK fertilizers on the growth and yield performances of three varieties of cowpea (FUAMPEA1, FUAMPEA2 and SAMPEA14). A field experiment was designed using the Randomized Complete Block Design of 3 blocks, 3 varieties, 3 treatments, and 5 replications. Plant spread varied between 25.5cm and 114.2cm with an average of 18.5 pods per plant. Number of leaves was significantly higher in FUAMPEA2 (133.5) than other varieties. FUAMPEA1 produced more branches (9.3) than other varieties. Application of NPK fertilizer significantly improved the plant spread (142.4cm) and the number of branches (8.5). Meanwhile, both NPK and HYS had equal effect on leaf length with values of 13.7cm and 13.2cm respectively but they performed better than CCT. Leaf width improved significantly in NPK (6.15 cm) more than compost. The number of flowers remained unvaried among the three varieties whereas varieties differed significantly in all other yield parameters. Number of pods varied between 10.6 pods in SAMPEA14 to 23.2 pods in FUAMPEA2. The latter produced longer pods (13.1cm) and heavier seeds (39.67g/100 seeds) than other varieties. Treatments produced varied responses on all yield parameters (p<0.05). Application of NPK fertilizer significantly influenced the number of pods, flowers and seed weight whereas CCT and HYS had equal effects on these parameters. Pod sizes were significantly higher in CCT (12.54cm), followed by HYS (11.98cm) while NPK produced the shortest pods. Seed sizes were the same in the treatments (p>0.05). The use CCT and HYS composts are recommended to supplement NPK fertilizer as treatments were found to enhance pod and seed sizes only while HYS had positive effects on leaf sizes. They could serve as potential sources of making organic compost to improve soil and enhance productivity of cowpea.